A cross-coupled LPF topology and design for millimeter-wave RFIC applications - Ma, Kaixue (2013)
A low-pass filter (LPF) with ultrawide rejection band and compact size by using a cross-coupled topology is proposed. The operating mechanism of the cross-coupled LPF from a unit cell to multiple cells is investigated by using the proposed circuit model. The topology and the circuit model are adopted to design the on-chip LPFs through parameter extracting and electromagnetic optimization. One of the designed cross-coupled LPFs with 1-dB cutoff frequency fc of 2.2 GHz demonstrates the stopband rejection of 30 dB up to 20 fc, i.e., 45 GHz, and the rejection of 20 dB up to 52 fc, i.e., 110 GHz. The measured passband insertion loss is less than 2.2 dB. The size of the LPF is only 350 μm by 280 μm or 0.0089 λg ×0.0071 λg (λg is the guide wavelength on silicon at cutoff frequency).